Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. The degree to which school principals practice transformational leadership and its relationship  to the level of risk and emergency management in schools in The Sultanate of OmanMr. Ali Hamad Al-Buraiki ,Dr. Youssef Nait Belaid2. The role of the school principal in professional development from the point of view of intermediate science and mathematics teachers in RiyadhMs. May Abdulaziz Al Abdulsalam, Dr. Saham Mohammed Kaaki3. Adaptive leadership among school principals and its relationship to the teaching self-efficacy  of intermediate school teachers in public schools in Mecca from the point of view of educational supervisorsMs. Salha Muhammad Abudahi4. The Factor Analysis and psychometric characteristics of the self-motivation scaling  and the Self-Efficacy scale of the sample of the school students in the Sultanate of OmanDr. Saif Darwish Alharrasi5. Psychological Resilience and Its Relationship with Rumor Perception in Electronic Social Media Among Women in Al-Madinah Al-MunawwarahMs. Amal Atiyat Allah Al-Mohammadi6. Intellectual stress as a predictor of Type D personality among a sample of graduate students at King Abdulaziz University in JeddahMs. Esraa Saad Alomari, Dr. Fatma Khalifa Elsayed7. Future scenarios for electronic training in Saudi universitiesMs. Tahani Ayed Alruhaimi, Ms. Manal Trekhem Alharthi, Ms. Noura Ibrahim Almohanna, Dr. Fatemah Abdalaziz Altuwaijri8. Evaluating the practices of student teachers in teaching mathematics  in resource rooms in JordanCo-Prof. Mohammad A. Beirat, Co-Prof. Hisham A. Almakanin, Co-Prof. Zaidan Alkhamaiseh
Keywords: Journal of Educational and Psychological Sciences